Innovative Way to Improve Learning Languange and Cultural Understanding Through Film Background Minangkabau Culture - Trisna Helda; Wahyudi Rahmat; Silvia Marni (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2021)
This article discusses how films set in Minangkabau culture can be used as an effective platform to enable students to understand Minangkabau culture and the target language. Through films, students broaden their understanding of culture, language, geography, sociolinguistics, socioeconomic, socio-political and educational in Minang society. This article describes how a small number of films set in Minangkabau culture have been used at different skill levels in language programs in schools as one of the local content subjects, especially schools located in West Sumatra with the majority of the Minang community. It also examines the role of films in the teaching and learning process, and how watching films strengthens classroom activities such as discussions, and debates and activities outside the classroom such as interviews and research on topics related to the films. To explore student feedback on this process, there was a discussion about responses to watching the film. It is proposed that three main issues need to be considered: film choice; development of lesson plans; and possible efficiency is obtained by asking students to watch movies. In conclusion, it is argued that the combination of these strategies demonstrates how films set in Minangkabau culture can be used in innovative ways to teach Minang language and culture in West Sumatra. Development of lesson plans; and possible efficiency is obtained by asking students to watch movies.